Homoclinic Orbits for a Class of Nonperiodic Hamiltonian Systems with Some Twisted Conditions - Qi Wang; Qingye Zhang (Abstract and Applied Analysis)
By the Maslov index theory, we will study the existence and multiplicity of homoclinic orbits for a class of asymptotically linear nonperiodic Hamiltonian systems with some twisted conditions on the Hamiltonian functions.